2022
DOI: 10.15406/mojabb.2022.06.00160
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Microsoft kinect skeletal tracking accuracy under varying external factors

Abstract: Focusing on its possible use in motion analysis, the accuracy of the Microsoft Kinect was investigated under various external factors including relative position, external IR light, computational power and large nearby surfaces. Two different experiments were performed that either focused on a general situation in an open room or when seated at a table. Results indicated that a large number of factors significantly affect the measurement error, but with only minor effect sizes, where the relative position and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Participants were also instructed to wear light-colored clothing during the examination. Secondly, viewing angles and position of the object might affect the measurement errors of Kinect sensor 26 , 27 . To deduce the error, Azure Kinect was placed right in frontal of the participants and as close as possible to the subject.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were also instructed to wear light-colored clothing during the examination. Secondly, viewing angles and position of the object might affect the measurement errors of Kinect sensor 26 , 27 . To deduce the error, Azure Kinect was placed right in frontal of the participants and as close as possible to the subject.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings indicated that obesity does not appear to restrict the Kinect sensor’s ability to track body joint locations. Finally, the Kinect software’s built-in assumptions and tracking algorithms for skeletal tracking may restrict the accurate placement of joint locations, leading to measurement errors 28 . As we lack knowledge about these assumptions and algorithms, we cannot prevent these errors.…”
Section: Discussionmentioning
confidence: 99%